Noninsect-Based Diet Leads to Structural and Functional Changes of Acidic Chitinase in Carnivora - Tabata, Eri; Itoigawa, Akihiro; Koinuma, Takumi; Tayama, Hiroshi; Kashimura, Akinori; Sakaguchi, Masayoshi; Matoska, Vaclav; Bauer, Peter O; Oyama, Fumitaka (Molecular biology and evolution, 2022)
Acidic chitinase (Chia) digests the chitin of insects in the omnivorous stomach and the chitinase activity in carnivorous Chia is significantly lower than that of the omnivorous enzyme. However, mechanistic and evolutionary insights into the functional changes in Chia remain unclear. Here we show that a noninsect-based diet has caused structural and functional changes in Chia during the course of evolution in Carnivora. By creating mouse-dog chimeric Chia proteins and modifying the amino acid sequences, we revealed that F214L and A216G substitutions led to the dog enzyme activation. In 31 Carnivora, Chia was present as a pseudogene with stop codons in the open reading frame (ORF) region. Importantly, the Chia proteins of skunk, meerkat, mongoose, and hyena, which are insect-eating species, showed high chitinolytic activity. The cat Chia pseudogene product was still inactive even after ORF restoration. However, the enzyme was activated by matching the number and position of Cys residues to an active form and by introducing five meerkat Chia residues. Mutations affecting the Chia conformation and activity after pseudogenization have accumulated in the common ancestor of Felidae due to functional constraints. Evolutionary analysis indicates that Chia genes are under relaxed selective constraint in species with noninsect-based diets except for Canidae. These results suggest that there are two types of inactivating processes in Carnivora and that dietary changes affect the structure and activity of Chia.
Keywords: Animals; Chitin; Chia; sekvence aminokyselin; chitin; Carnivora; digestive enzyme; Mice; Amino Acid Sequence; Dogs; myši; dieta; acidic chitinase; Diet; Chitinases; carnivores; chitinasy; zvířata; gene loss; psi; insectivores